Briquetting of Rosetta ilmenite ore with different organic binder and its reduction in hydrogen in the temperature range of 800÷1200 degrees of Celsius - Abd el-Gawad, Hala H.; El-Hussiny, Naglaa A.; Wassf, Marguerite A.; Kalifa, Mohamed G.; Iskander, Berlanty A.; Shalabi, Mohamed el-Menshawi H. (Wydawnictwa AGH, 2009)
Fine grained ilmenite ore was briquetted with different amounts of molasses or pitch and pressed under different values of pressure was studied in this investigation. The results show that optimal amount of added molasses and pitch were 1.5%, the pressure was fixed to 294.3 MPa. Furthermore, the characteristics of raw materials was examined by different methods of analysis, such as x-ray and screen analysis. The produced briquettes were then reduced by different amounts of hydrogen by different temperatures and the reduction kinetics was determined.

Drobno uziarniona ruda ilmenitu, brykietowana z różnymi ilościami melasy lub smoły pod różnym ciśnieniem, była przedmiotem badań w tym artykule. Wyniki wykazały, że optymalną ilością dodawanego lepiszcza było 1,5%, przy ciśnieniu 294,3 MPa. Ponadto, badano różnymi metodami, tj. promienie X oraz analiza sitowa, charakterystyki materiałów. Produkowane brykiety były redukowane przy udziale różnych ilości wodoru przy zmiennych wartościach temperatury. Kinetyka redukcji została określona.
Brykietowanie rudy ilmenitowej z Rosetta przy użyciu różnego organicznego lepiszcza redukowanego w atmosferze wodoru w zakresie temp. 800÷1200 stopni Celsjusza
Górnictwo i Geoinżynieria
Bibliogr. s. 39-40.
Keywords: ilmenite; reduction kinetics; kinetyka redukcji; briquetting; brykiety; reduction by hydrogen; redukcja w środowisku wodorowym